Acquisition and Generalization of Complex Empathetic Responses Among Children with Autism - Argott, Paul J. (Behav Anal Pract, 2017)
Empathy can be defined as a social interaction skill that consists of four components: (1) a statement voiced in the (2) appropriate intonation, accompanied by a (3) facial expression and (4) gesture that correspond to the affect of another individual. A multiple-baseline across response categories experimental design was used to evaluate the effectiveness of a prompt sequence (video modeling, in vivo modeling, manual and verbal prompting) and reinforcement to increase the frequency of complex empathetic responding by four children with autism. The number of complex empathetic responses increased systematically with the successive introduction of the treatment package. Additionally, generalization was demonstrated to untaught stimuli and a novel adult. Responding maintained over time to varying degrees for all participants. The data illustrate that children with autism can be taught using modeling, prompting, and reinforcement to discriminate between categories of affective stimuli and differentially respond with complex empathetic responses.